A town is born : the Fitzroy Crossing story - Hawke, Steve, 1959- (Magabala Books, 2013)
In the course of a couple of years the township of Fitzroy Crossing in the remote Kimberley changed from a tiny frontier outpost, to a refugee camp with hundreds of people living in fringe camps in third world conditions. From this maelstrom a unique community emerged, with a strong ethos of cooperation and support amongst the various peoples of the Fitzroy Valley.